Pre-service teachers' perceptions of physical, socioemotional and cognitive traits in gifted students: unveiling bias? - Carmen Ferrándiz; Mercedes Ferrando-Prieto; Álvaro Infantes-Paniagua; Álvaro Infantes-Paniagua; Maria Carmen Fernández Vidal; Rosa María Pons (Frontiers in Sports and Active Living)
IntroductionAttitudes and beliefs guide our decision-making. In the educational context, prior research has noted the existence of prejudices and stereotypes among teachers that make it difficult to identify and care for gifted students. Stereotypes towards gifted students can hinder the identification and development of potential and the development of personality. This study examines Spanish pre-service teachers' stereotypical conceptions of gifted and non-gifted students focusing on physical appearance and athletic ability.MethodsFollowing a mixed methods research with between subjects design and using a convenience sampling, 455 last-year pre-service teachers enrolled during 2023–2024 in one of three university degrees or one Master's degree related to teacher training at University of Murcia were randomly assigned a vignette in order to rate the intellectual ability, motivation, prosociality, and physical characteristics of a fictitious 12-year-old student whose ability level (gifted/non-gifted) and gender (girl/boy), varied. Additionally, participants were asked to describe how they imagined the fictitious student's physical appearance. After exploring measurement invariance (SPSS AMOS 29), a MANCOVA was performed to compare the results across vignettes (SPSS 28). The study delves specifically into the physical characteristics attributed to gifted students through qualitative analysis addressing co-occurrence coefficients (Atlas.ti 9).ResultsThe results suggest that pre-service teachers described gifted students as more intelligent and with better physical attributes, especially gifted females. Furthermore, gifted students of both genders were defined as more intelligent, creative, and tall. They considered gifted girls to be attractive and gifted boys to be good at sports, highly fit, formally dressed, and wearing glasses.DiscussionThe results are relevant as they allow a greater understanding of the perception of these students. As pointed out by pioneering studies in the field, implicit theories relate intelligence to physical appearance. This evidence could improve the training of future teachers, and therefore, the identification and assessment of gifted students from different areas.